Artificial neural network scheme to solve the hepatitis B virus model - Haider, Qusain; Hassan, Ali; Eldin, Sayed M. (Frontiers in Applied Mathematics and Statistics, 2023)
This article aims to describe the simulation studies of the hepatitis B virus nonlinear system using supervised neural networks procedures supported by Levenberg-Marquardt back propagation methodology. The proposed strategy has five distinct quantities: susceptible , symptomatic infections , chronic infections , recovered population , and a population that has received vaccinations . The reference data set for all three distinct cases has been obtained utilizing the ND-Solver and Adams method in Mathematica software. The outcomes have been validated with performance plots for all cases. To check the accuracy and effectiveness of proposed methodology mean square error has are presented. State transition, and regression plots are illustrated to elaborated the testing, training, and validation methodology. Additionally, absolute errors for different components of hepatitis B virus model are demonstrated to depict the error occurring during distinct cases. Whereas the data assigned to training is 81%, and 9% for each testing and validation. The mean square error for all three cases is this show the accuracy and correctness of proposed methodology.